Overcoming Challenges in Digital Public Service Delivery: Insights from Lapak Aduan Implementation - Etin Indrayani; Fergie Akbar; Suhajar Diantoro (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2025)
The Banyumas Regency Government provides services to the community and establishes interactive government and public services through a public communication space called "Lapak Aduan." In practice, Lapak Aduan, which utilizes social media platforms, serves as a bridge for the public to interact with the relevant local government agencies, with a maximum response time of 3 hours. However, Lapak Aduan often fails to meet the specified response time for public complaints, and the lack of public engagement has led to low utilization of the complaint platform. This research aims to identify the reasons for the public's lack of interest in the Lapak Aduan application and improve Lapak Aduan's service standards. This study adopts a qualitative research method, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that the Lapak Aduan application still has numerous shortcomings in terms of usefulness and ease of use, hindering its ability to facilitate public digital complaint services. Consequently, the public's interest in utilizing Lapak Aduan remains low, necessitating periodic socialization efforts to ensure that the community can fully benefit from its convenience.